2017
DOI: 10.5942/jawwa.2017.109.0035
|View full text |Cite
|
Sign up to set email alerts
|

The Water Infrastructure Finance and Innovation Act of 2014: Structure and Effects

Abstract: Many US municipalities confront serious challenges due to aging water and wastewater infrastructure. Many systems require immediate repairs, upgrades, and replacement, but available funding is scarce. Readily available low‐interest financing is of great help to such municipalities. The Water Infrastructure Finance and Innovation Act (WIFIA) approved by Congress in 2014 was a step in that direction. WIFIA is a five‐year pilot program focused on supporting large‐scale projects that may be under‐served by existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The minimum project sizes are $5 million for communities serving 25,000 people or fewer, and $20 million for communities serving more than 25,000 people. Borrowers can meet these requirements by combining multiple smaller projects under a single loan with a common security pledge (EPA 2024(EPA , 2023(EPA , 2020Gebhardt et al 2022;Humphreys 2020;Ryan 2023Ryan , 2020OECD 2017;Vedachalam & Geddes 2017).…”
Section: General Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum project sizes are $5 million for communities serving 25,000 people or fewer, and $20 million for communities serving more than 25,000 people. Borrowers can meet these requirements by combining multiple smaller projects under a single loan with a common security pledge (EPA 2024(EPA , 2023(EPA , 2020Gebhardt et al 2022;Humphreys 2020;Ryan 2023Ryan , 2020OECD 2017;Vedachalam & Geddes 2017).…”
Section: General Termsmentioning
confidence: 99%
“…The Water Infrastructure Finance and Innovation Act (WIFIA) program (PL 113-121 2014) supplements SRFs with broader project eligibility and annual federal funding sufficient to support loans for much larger projects. (EPA 2024(EPA , 2023(EPA , 2020Gebhardt et al 2022;Humphreys 2020;Vedachalam & Geddes 2017)…”
mentioning
confidence: 99%
“…Researchers have suggested that PPP-enabling laws have the effect of increasing private investment in infrastructure (Albalate et al , 2018). Examples include the recently-introduced Water Infrastructure Finance and Innovation Act (WIFA) in the USA (Vedachalam and Geddes, 2017). Researchers have suggested that PPPs have been utilised as a vehicle of economic rationalisation in the public-service utilities infrastructure space (Greve and Hodge, 2018).…”
Section: Water Governance In the Usa: Its Forms And Modalitiesmentioning
confidence: 99%
“…The funding and government capital constraints led to the passage in 2014 of the WIFA. This act explicitly calls for increased federal funding for PPPs undertaking projects in water infrastructure (Vedachalam and Geddes, 2017). The legislation underlines the extent to which funding for new water infrastructure and repairs ultimately comes from the public sector, even when it involves private-sector financing.…”
Section: Water Governance and The Accountability Gapmentioning
confidence: 99%
See 1 more Smart Citation